A sustainable calcined water treatment sludge and rice husk ash geopolymer. (15th April 2016) - Nimwinya, Ekkasit; Arjharn, Weerachai; Horpibulsuk, Suksun; Phoo-ngernkham, Tanakorn; Poowancum, Anurat
Abstract: Geopolymer is an environmentally friendly cementing agent and is an alternative to Ordinary Portland Cement (OPC). Calcined Water Treatment Sludge (WTS) and Rice Husk Ash (RHA) blends are used as a sustainable precursor for developing a lightweight geopolymer binder in this research. The alkali activator is a mixture of sodium hydroxide (NaOH) and sodium silicate (Na2 SiO3 ). The effects of the SiO2 /Al2 O3 ratio, which reflects the characteristics of chemical compositions of WTS and RHA, and the heat-curing temperature (at room temperature and 60 °C) on density, setting time and Unconfined Compressive Strength (UCS) are investigated. It is evident from this study that the density of WTS–RHA geopolymers at various SiO2 /Al2 O3 ratios and temperatures is essentially the same and is approximately 3 times lower than that of OPC (of 3.15 g/cm 3 ). The SiO2 /Al2 O3 ratio and temperature significantly affect the setting time and UCS. A higher SiO2 /Al2 O3 ratio results in longer initial and final setting times as the condensation rate between silicate and aluminate species is faster than that between silicate and silicate species. The optimum SiO2 /Al2 O3 ratio providing the highest strength is found at approximately 4.9 and 5.9 for room temperature and 60 °C curing conditions. At these optimum SiO2 /Al2 O3 ratios, the UCSs of geopolymers meet the minimum requirement for OPC of 19 MPa. This research will enable WTS and RHA traditionally destined for landfills to be used in a sustainable manner as a precursor in geopolymer binders. This sustainably, in terms of economic and environmental perspectives, is also analyzed and discussed in this paper.